Aplikasi Pendaftaran Seminar dan Sertifikat Online pada STIKOM Uyelindo Kupang - Marisa Martha; Emanuel Safirman Bata (JITU : Journal Informatic Technology And Communication, 2023)
College of Computer Informatics Management (STIKOM) Uyelindo Kupang is an IT-based school that has been established since 2000. STIKOM Uyelindo Kupang often holds many activities, one of which is seminars. Problems that arise when carrying out seminars that use many third-party applications such as Google Forms, Photoshop, WhatsApp, or Google Drive for registration of seminar participants, filling in attendance lists, recording participant attendance data, making certificates, and sending certificates so that they are less effective and efficient. The next problem is manually collecting data on seminar participants in attendance. Then the admin will enter the participant's name into the certificate manually. This will take time and require a large enough storage to store the certificate files that have been created. Another problem is that duplication of seminar certificate data can occur, due to the absence of certificate data validation. Therefore an application is needed that can solve existing problems to facilitate the process of running seminar activities. The purpose of this research is to build an online seminar application that can help with seminar activities that will be held at STIKOM Uyelindo Kupang using the Waterfall Method. The expected end result of this research is to be able to build online seminar and certificate registration applications which can later assist in the process of seminar activities which cover all seminar activities.